ZnO nanorods anchored SnS through successive ionic layer adsorption and reaction (SILAR) approach for enhanced performance photoelectrochemical cell - Tan, Huey Jing; Zainal, Zulkarnain; Talib, Zainal Abidin; Lim, Hong Ngee; Shafie, Suhaidi; Tan, Sin Tee; Bahrudin, Noor Nazihah (Elsevier, 2025)
Two-dimensional (2D) metal dichalcogenides such as tin sulfide (SnS) are gaining considerable research interest in photoelectrochemical (PEC) cell applications. However, challenges remain in chemically producing a p-n SnS/ZnO heterojunction where the SnS photosensitizing layer at sufficient low band gap energy can be deposited without damaging the ZnO part. In this study, SnS-sensitized ZnO nanorods (NRs) thin films were prepared using facile hydrothermal and successive ionic layer adsorption and reaction (SILAR) methods. It is demonstrated that the phase, morphology, and orientation of a SILAR deposited SnS thin film are strongly determined by the combined effect of film thickness and annealing temperature. At low SILAR cycle number, the polycrystalline SnS thin films have mainly occurred in orthorhombic phase based on the X-ray diffraction (XRD) analysis. Increasing the SILAR cycle generates also cubic π-SnS which is later quenched by high-temperature thermal treatment. Field-emission scanning electron microscopy (FESEM) shows the change in grain size and SnS distribution on the surface of ZnO NRs at different film thickness and annealing temperatures, which in turn affected the optical and photoelectrochemical properties of SnS/ZnO heterojunctions. Ultraviolet-visible (UV–Vis) spectroscopy, photoluminescence (PL) spectroscopy and linear sweep voltammetry (LSV) studies confirmed the improved visible incident photons harvesting and a lower carrier recombination after the construction of p-n SnS/ZnO heterostructures. As compared to the pristine ZnO photoelectrode that displays a low conversion efficiency (η) of 0.40 %, the optimized SnS/ZnO NRs sample exhibited a maximum η of 1.33 % at +0.2 V (vs. Ag/AgCl).